2021
DOI: 10.1055/s-0041-1731073
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin Efficacy versus Ferrous Sulfate in Treatment of Children with Iron Deficiency Anemia

Abstract: Lactoferrin (LF) is an iron-binding globular glycoprotein that is structurally and chemically similar to serum transferrin. Many studies have been done to evaluate the effect of oral LF administration on iron deficiency anemia (IDA) with controversial results. This study was designed to compare the efficacy of LF versus oral ferrous sulfate (OFS) therapy in the treatment of children with IDA. A significant increase in mean hemoglobin and serum iron concentrations was noted in the group that received oral bovin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Higher Hb level in infants of the bLF 91.5 group than those in the other two groups at 3 months of intervention Mikulic et al ( 2020 ) RSBCT 26 infants without severe anemia, 3–6 months (Kenya) 1.41 g apo-bLF + FeSO 4 , 1.41 g holo-bLF FeSO 4 28 days Higher fractional iron absorption from the meal containing FeSO 4 with apo-bLF than from the meal containing FeSO 4 or holo-bLF Atia et al ( 2021 ) ROT 40 obese children with IDA, 6–18 year (Egypt) 100 mg Ferric hydroxide polymaltose 3 months Higher Hb, MCV, MCH, serum ferritin, serum iron, and transferrin saturation, and lower IL-6. No difference in hepcidin between the groups, but significant reduction was observed in the bLF group compared to that before intervention El-Asheer et al ( 2021 ) ROT 105 children with IDA, 2–15 years (Egypt) 100 mg ± iron sachet Ferrous sulfate 30 days Higher values of hematological parameters (RBC, Hb, Ht, MCV, MCH, serum iron, and reticulocyte) in the bLF/bLF + iron group compared with the iron group. Fewer adverse effects in the bLF group El-Hawy et al ( 2021 ) RCOT 120 children with IDA, 1–18 years (Egypt) 100–200 mg ± iron sachet FeBC, IPC 1 month Improved iron status in the FeBC and IPC groups compared with the bLF group, but no difference compared with the bLF + iron group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher Hb level in infants of the bLF 91.5 group than those in the other two groups at 3 months of intervention Mikulic et al ( 2020 ) RSBCT 26 infants without severe anemia, 3–6 months (Kenya) 1.41 g apo-bLF + FeSO 4 , 1.41 g holo-bLF FeSO 4 28 days Higher fractional iron absorption from the meal containing FeSO 4 with apo-bLF than from the meal containing FeSO 4 or holo-bLF Atia et al ( 2021 ) ROT 40 obese children with IDA, 6–18 year (Egypt) 100 mg Ferric hydroxide polymaltose 3 months Higher Hb, MCV, MCH, serum ferritin, serum iron, and transferrin saturation, and lower IL-6. No difference in hepcidin between the groups, but significant reduction was observed in the bLF group compared to that before intervention El-Asheer et al ( 2021 ) ROT 105 children with IDA, 2–15 years (Egypt) 100 mg ± iron sachet Ferrous sulfate 30 days Higher values of hematological parameters (RBC, Hb, Ht, MCV, MCH, serum iron, and reticulocyte) in the bLF/bLF + iron group compared with the iron group. Fewer adverse effects in the bLF group El-Hawy et al ( 2021 ) RCOT 120 children with IDA, 1–18 years (Egypt) 100–200 mg ± iron sachet FeBC, IPC 1 month Improved iron status in the FeBC and IPC groups compared with the bLF group, but no difference compared with the bLF + iron group.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of infants who were previously exclusively breastfed and assumed to be at a high risk of anemia, after 3 months of bLF intervention, the iron status, including Hb, serum ferritin, transferrin receptor-ferritin (TFR-F) index, and total body iron content (TBIC) was improved, leading to a lower prevalence of anemia, iron deficiency (ID), and iron deficiency anemia (IDA) (Chen et al 2015a ). In addition, several studies on anemic children have shown that bLF consistently improved the iron status (El-Khawaga and Abdelmaksoud 2019 ; Chen et al 2020 ; Mikulic et al 2020 ; Kamal et al 2021 ; El-Asheer et al 2021 ; Omar et al 2021 ; Atia et al 2021 ). A recent meta-analysis of studies on pregnant women suggested that bLF improved IDA (Abu Hashim et al 2017 ), and these findings are consistent with the results obtained from studies on children.…”
Section: Resultsmentioning
confidence: 99%
“…This represented 68% of all participants involved in the trials [ 19 , 21 – 23 , 25 , 26 , 28 , 29 , 33 – 35 ]. Seven trials (37%) involved children aged over 2 [ 24 , 27 , 30 – 32 , 36 , 37 ], and one trial targeted cancer patients undergoing chemotherapy [ 20 ]. Additionally, four trials included 334 individuals with chronic health conditions (cancer, cerebral palsy, inflammatory bowel disease, obesity), all of whom had anemia (Hb < 11.5 g/dL) [ 20 , 27 , 32 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the 1353 participants in the intervention groups, all received oral bLF. They were compared to the following groups: 1160 received ferrous sulfate [ 21 , 22 , 24 – 29 , 33 , 34 , 38 ], 73 received ferric gluconate [ 20 ], 73 received ferrous fumarate [ 35 ], 30 received ferrous bisglycinate [ 30 ], 70 received ferric (III) hydroxide polymaltose [ 31 , 37 ], 62 received iron polymaltose complex [ 30 , 32 ], 33 received iron (III) hydroxide dextran complex [ 23 ], and 112 received a combination of LF and iron [ 24 , 30 , 31 ]. The bLF dosage ranged from 100 to 250 mg per day, and the treatment duration varied between 30 and 90 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation